The Influence of Production Value, Wages and Number of Business Units on Labor Absorption in the Industrial Sector with Investment as a Moderating Variable in East Java Province for the Period 2019-2024 - Sandi, Farid Kurnia; Jatmiko, Anang Rohmad; Rohman, Mohamad Fathur (Riwayat: Educational Journal of History and Humanities, 2025)
This study analyzes the effect of production value, wages, and number of business units on labor absorption in the industrial sector in East Java Province during the period 2019-2024. The role of investment as a moderating variable is also tested in this relationship. The data used are secondary data sourced from the Central Statistics Agency of East Java Province with a sample size of 28 regencies and cities. The analysis method uses a quantitative approach using the Structural Equation Modeling (SEM) method using the Analysis of Moment Structures (AMOS) software. The results of the study through hypothesis testing indicate that production value, wages and number of business units have a positive and significant effect on labor absorption. Moderation analysis reveals that investment has a positive value in moderating the relationship between production value, wages and number of business units on labor absorption. The implications of this study indicate that increasing production value, wages, number of business units and investment have a crucial role in job creation. Therefore, policies on production value, wages, number of business units and investment need to be considered and maintained so as not to hinder labor absorption. The limitations of this study are the limited scope of variables and the sample data period.